2001
DOI: 10.1530/rep.0.1210217
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of adenylyl cyclases in cultured human granulosa cells

Abstract: Granulosa cells play an essential role in follicular development and formation of corpora lutea. Many functions of granulosa-lutein cells are controlled by activation of G protein-coupled receptors and the formation of cyclic AMP (cAMP) by adenylyl cyclase. There are at least nine mammalian adenylyl cyclase isoenzymes, which show different sensitivities towards other signalling systems. The aim of this study was to identify the types of adenylyl cyclase present in human granulosa cells and to investigate its f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…No ACI expression was observed in thecal cells. The observed expression of ACI, ACIV, and ACVIII in this study is consistent with that seen in cultured human granulosa cells obtained from antral follicles (Asbóth et al, 2001). However, unlike in the cultured human granulosa cells (Asbóth et al, 2001), where no staining for ACII was observed, we observed specific ACII staining in granulosa cells, which appear to increase in intensity in response to eCG administration.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…No ACI expression was observed in thecal cells. The observed expression of ACI, ACIV, and ACVIII in this study is consistent with that seen in cultured human granulosa cells obtained from antral follicles (Asbóth et al, 2001). However, unlike in the cultured human granulosa cells (Asbóth et al, 2001), where no staining for ACII was observed, we observed specific ACII staining in granulosa cells, which appear to increase in intensity in response to eCG administration.…”
Section: Discussionsupporting
confidence: 92%
“…The observed expression of ACI, ACIV, and ACVIII in this study is consistent with that seen in cultured human granulosa cells obtained from antral follicles (Asbóth et al, 2001). However, unlike in the cultured human granulosa cells (Asbóth et al, 2001), where no staining for ACII was observed, we observed specific ACII staining in granulosa cells, which appear to increase in intensity in response to eCG administration. As the stimulation of ACII is primarily regulated by the simultaneous presence of both G sα and G βγ subunits (Gao and Gilman, 1991), G protein‐coupled receptor agonists might play an important role in the regulation of this enzyme in granulosa and luteal cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The presence of multiple tmAC transcripts in the testis is not surprising, given the heterogeneous cell population, and is consistent with findings in other tissues. For example, in the brain (Mons et al 1998), nephron (Bek et al 2001), lung (Jourdan et al 2001) and myometrium and cultured granulosa cells (Price et al 2000;Asboth 2001), multiple tmAC are localized in distinct regions and cells. This suggests that the synthesis of cAMP in the testis is multiply regulated, as it is in other tissues.…”
Section: Discussionmentioning
confidence: 99%